Efektivitas pencahayaan alami melalui desain bukaan atas pada model bangunan bervolume besar - Ariani Mandala; E. B. Handoko Sutanto; Amirani Ritva Santoso (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2021)
The utilization of daylighting as an effort to reduce the usage of building energy needs to be optimized. This is because, low-rise buildings with large volumes require specific strategies for proper light distribution throughout the space. Hence, this study aims to explore and compare the effectiveness of daylighting in the openings design of skylight, roof monitor, and sawtooth in large-volume buildings in Bandung. The effectiveness is assessed by examining lighting performance based on distribution patterns, the value of Daylight Factor (DF), and the Coefficient of Uniformity (CU). Experimental research method with simulation program known as Velux Daylight Visualizer 3.0 is used to present and analyze the lighting data. The results showed that the type, position (openings' height and distance), as well as the opening direction affected the distribution patterns and daylighting performance. Based on the simulation, the skylight opening is the most effective in meeting the standard value of Daylight Factor (> 2%) and Coefficient of Uniformity (CU min. 0.3 and DF min. 0.8%). Thus, space and openings model with a percentage roof area of 16.3% in the simulation can be used as a reference for large-volume buildings because, it meets the requirements of Daylight Factor value and sufficient Coefficient of Uniformity.